Supersaturated split-plot design. - Koh, Woon Yuen (Journal of Quality Technology)
Methods to construct supersaturated split-plot designs (SSSPDs) are presented. We use an E(s2)-optimal supersaturated design (SSD) in the whole-plot and half fractions of Plackett-Burman designs (PBDs) in the same plot. It is shown that (1) the resulting split-plot design has orthogonal columns, (2) the split-plot columns are orthogonal to the whole-plot columns and (3) the whole plot columns are orthogonal to the whole plot by split plot interactions. As an example, an SSSPD is applied to an extrusion process to produce biodegradable packaging forms, and data are analyzed using stepwise selection procedures. It is concluded that SSSPD can be used productively as a screening design when the experiment has a split plot structure and traditional designs are not feasible.